2001
DOI: 10.1152/jappl.2001.90.3.933
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine enhances aerobic exercise capacity in association with augmented nitric oxide production

Abstract: We tested whether supplementation with L-arginine can augment aerobic capacity, particularly in conditions where endothelium-derived nitric oxide (EDNO) activity is reduced. Eight-week-old wild-type (E(+)) and apolipoprotein E-deficient mice (E(-)) were divided into six groups; two groups (LE(+) and LE(-)) were given L-arginine (6% in drinking water), two were given D-arginine (DE(+) and DE(-)), and two control groups (NE(+) and NE(-)) received no arginine supplementation. At 12-16 wk of age, the mice were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 31 publications
4
41
0
Order By: Relevance
“…36) affect V O 2 max . On the other hand, the two studies investigating V O 2 max and RER in C57BL/6J, age and test protocol as the present study, found similar results (12,27).…”
Section: Discussionsupporting
confidence: 86%
“…36) affect V O 2 max . On the other hand, the two studies investigating V O 2 max and RER in C57BL/6J, age and test protocol as the present study, found similar results (12,27).…”
Section: Discussionsupporting
confidence: 86%
“…In these animals, L-arginine supplementation increases exercise capacity in association with an increase in limb blood flow and urinary nitrogen oxides. 36 In addition to its action as a vasodilator, NO mediates angiogenesis. In the NO synthase-deficient mouse, angiogenesis in response to limb ischemia is impaired, as demonstrated by capillary densitometry.…”
Section: Wilson Et Al L-arginine In Peripheral Arterial Diseasementioning
confidence: 99%
“…17). Administration of L-arginine normalizes aerobic capacity (18) and reduces fat mass in Zucker diabetic fatty rats (19). The lack of appropriate generation of endogenous NO is an important progression factor of atherosclerosis in mice (20) and L-arginine may reduce atherogenesis in hypercholesterolemic mice (21).…”
mentioning
confidence: 99%